PENGARUH MEDIA KARTU ANGKA TERHADAP KEMAMPUAN BERHITUNG SISWA KELAS II SD NEGERI 74 BONTORITA II - Hajrawati; Nurul Aulia Bahri; Syamsuriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using number card media on elementary school students’ numeracy skills. The background of this research arises from the issue of low student performance in basic arithmetic, which is caused by the lack of varied teaching methods and limited use of concrete media in the learning process. This research employed a quantitative approach with a pretest–posttest design. The sample consisted of two-grade students at UPT SDN 74 Bontorita II. Data were collected through numeracy tests administered before and after the implementation of number card media. The findings revealed a significant improvement in students’ numeracy skills after the use of number card media. The number card media proved effective in enhancing conceptual understanding, increasing student motivation, and creating a more interactive and enjoyable learning environment. Therefore, number card media can serve as an effective alternative learning tool to improve elementary school students’ numeracy skills.